Perbedaan Kadar Pentraxin 3 pada Penderita Hepatitis B Kronis dengan Cirrosis dan Tanpa Cirrosis - Sasmita, Afrianda Wira; Sungkar, Taufik; Loesnihari, Ricke (Journal of Telenursing (JOTING), 2023)
This study aims to see differences in pentraxin 3 levels in chronic hepatitis B sufferers with cirrosis and without cirrosis. The method uses cross sectional consecutive sampling. The results of this study found a significant difference between the average value of Pentraxin 3 in chronic Hepatitis B patients with liver cirrhosis group compared to the group without liver cirrhosis (p<0.001). There was a significant difference between the Pentraxin 3 levels in the group of Chronic Hepatitis B sufferers with liver cirrhosis compared to the group of Chronic Hepatitis B sufferers without liver cirrhosis (p<0.001) where the Pentraxin 3 levels in the Chronic Hepatitis B group with liver cirrhosis were higher compared to the group without liver cirrhosis. In conclusion, Pentraxin 3 levels can be used as an alternative marker to assess the development of liver cirrhosis in Chronic Hepatitis B patients. Keywords: Chronic Hepatitis B, Liver cirrhosis, Pentraxin 3